Le Journal de Virginia Woolf ou l’invention d’une voix « à soi » - Sandra Cheilan (Itinéraires, 2012)
Virginia Woolf used her diary as a personal testimony and analysis of history, where privacy and politics intertwined. The intimist style of her diary had a polemical dimension: it consisted of fighting against official political speeches of a patriarchal society. The speech from “inside” was a subversion of the official and dominant kind: it was a place of another type even marginal of political discourse. We will study three characteristics of Woolf’s diarist writing as the invention of a new political view: the subjectivation of political facts, the disqualification of prevailing views, and the creation of a voice of “one’s own,” an independent voice. The diary updates a “feminist writing” of politics, in contradiction with ideologies and values of Woolf’s contemporary society.